Assessing youth sprint ability - methodological issues, reliability and performance data - Rumpf, M. C.; Cronin, J. B.; Oliver, J. L.; Hughes, M. (Pediatric Exercise Science, 2011)
The primary purpose of this paper was to provide insight into the methodological issues and associated reliability of assessments used to quantify running sprint ability in youth athletes aged 8-18 years. Over-ground sprinting was the most reliable and common used choice of assessment to measure sprint performance of youth. In addition, the performance data of those athletes over distances ranging from 5 to 40 meters was collated from 34 published articles and tabulated with regards to the athlete`s chronological age. Torque or nonmotorized treadmills have been used to quantify sprint performance in youth with acceptable reliability, this technology providing deeper insight into sprint kinetics and kinematics; however there is limited performance data on youth using the torque and the nonmotorized treadmill. It is suggested that future research should use this technology in youth to better understand changes associated with growth, maturation and training.